Effect of Endo-Z bur or Bladesonic ultrasonic tip on the adaptation of filling material. A micro-CT study - Fiorin de Souza, Pedro Henrique [UNESP]; Santos-Junior, Airton Oliveira [UNESP]; Pinto, Jáder Camilo; Carita Tavares, Karina Ines Medina [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2023)
This study aimed to evaluate the effect of apicoectomy performed with a bur or an ultrasonic tip on the adaptation of the filling material to root canal dentin. Twenty human mandibular incisors were selected and prepared with a ProDesign Logic system up to diameter 40/.05. The root canals were filled with Bio-C Sealer (Angelus, PR, Brazil) using the single cone technique and were stored at 37°C and 95% relative humidity for 7 days. After this period, the apicoectomy of the 3 millimeters of the root apex was performed using Endo-Z bur (Dentsply Sirona) or Bladesonic ultrasonic tip (Helse Ultrasonic, Santa Rosa de Viterbo, Brazil) (n=10). The specimens were scanned by microcomputed tomography (micro-CT; SkyScan 1176) with a voxel size of 8.74 μm after obturation and after apicoectomy. The percentage of voids at the interface between the filling material and the root canal wall was evaluated in the apical 4 mm of the root after apicoectomy, besides the time cutting to both devices. The data obtained were submitted to paired and unpaired t-tests (α = 0.05). Endo-Z and Bladesonic increased the percentage of voids between the filling material and the dentin after apicectomy (p<0.05), and they were similar (p>0.05). Endo-Z has a shorter time to perform apicoectomy compared to Bladesonic (p<0.05). Apicectomies with Endo-Z or Bladesonic could harm the material/dentin interface, while the Endo-Z bur was faster than the Bladesonic ultrasonic tip.
Keywords: apicoectomy; endodontics; ultrasound; x-ray microtomography